Investigating the integration of SMEs' information systems: an exploratory case study. (1st September 2004) - Themistocleous, Marinos; Chen, Hsin
The need for business to exchange real-time information has grown since the adoption of e-commerce technology. To address this need, organisations might have to integrate their IT infrastructures. Until now, integration is frequently cited as being a sore point within organisations. For small- and medium-sized entrepreneurships (SMEs), integration is a significant problem due to high costs and technology requirements. Some cases show that SMEs can improve their competitiveness by integrating their systems with their suppliers, or other trading partners. Existing approaches to integration like electronic data interchange (EDI) might support SMEs to overcome part of the integration problems but they have their limitations. Today, web services can be exploited to further simplify unadorned integration problems. This paper presents an investigation and analysis on the integration of SMEs by reviewing the normative literature. In addition, a case study was conducted to explore the integration efforts of SMEs and understand how they respond to integration problem.